Molecular Characterization, Phytochemical Analysis, Antioxidant and Anticancer Potentials of Wrightia tinctoria - Angamuthu, Sudha (International Journal of Pharmaceutical & Biological Archive, 2018)
In worldwide the use of the plant materials to prevent and treat infectious diseases successfully over the years has attracted the attention of scientists. Plant based anticancer/antioxidant compounds can serve the purpose without any side effects often associated with synthetic drugs and also little chance of development of resistance. The importance of the antioxidant constituents of plants in the protection from dreadful disease like cancer is also raising interest among scientists. In the current study the phytoconstituents in the Wrightia tinctoria, plant leaf extracts were analysed and estimated using qualitative and quantitative phytochemistry. The scavenging activity (antioxidant activity) was determined using DPPH method and it was found that water extract had the highest antioxidant activity, i.e., 27.14% while for methanol extract, it’s the least, i.e., 9.72% and for chloroform extract, it is 19.27%. MTT assay was performed to understand the cytotoxicity of the extracts against liver cancer cell lines HepG-2.The cancer cells were treated with methanol extract at three different concentrations of 100μg, 500μg and 1000μg. The result obtained was then compared with control and positive control (cancer cells were treated with anticancer drug- Cyclo-90) and it was found that at the concentration of 1000μg, anticancer activity was highest and effective and the percentage toxicity was found to be 76.54% which is very close to that of Cyclo-90 drug, i.e., 77.74%. This leads to the conclusion that, due to its highly important medical nature was then subjected to molecular characterization to generate a DNA barcode. The matK gene was used as a marker and was amplified by PCR. The amplicons were subjected to DNA sequencing and the sequences so obtained were subjected to sequence alignment using BLAST tool. From this, Wrightia tinctoria has been identified to possess the anti-cancer property and can be used for curing cancer.